Letter (copy) : Leaflet - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0117-001 15th September, 1937. The Secretary, Spanish Medical Aid Committee, 24/28, New Oxford Street, LONDON, W.C.2. Dear Sir, (or Madam) LEAFLET. I notice enclosed with the copy of the last Minutes an appeal leaflet " Medical Aid For Spain ", issued apparently on behalf of the Committee, and with my name attached. I hope you will allow me to express my astonishment that a document of this kind should have been prepared and published with my name attached without a draft copy being at any time submitted to me for review or approval. I notice too that in the third illustration a reference is made to Huete under the description "Our Base Hospital on the Madrid Front." I would like to point out to the Committee that I have previously objected in Committee to any suggestion that the Committee is responsible in any way for the Huete hospital, and I know of no resolution passed by the Committee which entitles a description of Huete as "Our Base Hospital on the Madrid Front." It is especially astonishing to me when I have previously opposed this description to find it included in the leaflet, with my signature attached without my authority, approval or any intimation to me. I have formally to ask that this appeal be withdrawn and a new leaflet prepared, and I hope it will not be taken amiss if I object to the way in which my name has been used in this matter without my knowledge. I consider this premature publication deplorable. Yours faithfully, Chairman. Spanish Medical Aid Committee. 292C/946/2/117